Hands-on, Eyes-on: Enhancement of Nigerian Senior Secondary School Physics Through Observational Learning - Abiodun A Bada; Akinyemi O Akinbobola (International Journal of Pedagogy and Teacher Education, 2022)
Physics is an aspect of science that is essential for the scientific development of any nation, but the performance of students in the subject remains a concern for physics educators. Observational learning is one way of enhancing performance. This study investigates the effects of this type of learning as reinforcement to enhance Nigerian students’ performance in physics. The investigation adopted the pre-test post-test randomized control group quasi-experimental design involving 89 senior school students randomly selected from two schools in Ondo, Nigeria. The instrument, the Physics Achievement Test in Energy Quantization (PATEQ), consisting of 19 multiple choice questions, was used to obtain the data. PATEQ was validated by three science education experts and a reliability coefficient of 0.72 was achieved through Kuder-Richardson Formula 21. The experimental and control groups were taught energy quantization using observational and conventional teaching methods respectively. The findings show that observational learning has a significant effect on physics students’ achievement. It is concluded that such learning should be used to reinforce the teaching of physics in order to improve Nigerian students’ grades in the subject.